Synthesis, Growth and Characterization of Semi-organic Nonlinear Optical Crystal: Glycine Zinc Chloride - S. Ponnusamy2; J. Thomas Joseph Prakash3, M. Iyanar1; C. Muthamizhchelvan2* (Recent Research in Science and Technology, 2010)
Abstract Semi-organic single crystals of glycine zinc chloride (GZC) have been grown by slow evaporation solution growth technique. The crystal system has been identified and lattice dimensions have been measured from the single crystal X-ray diffraction analysis. FTIR analysis was used to estimate qualitatively the presence of the functional groups in the grown crystal. Its linear optical character has been assessed by UV-visible analysis and found that there is no absorption in the entire visible region. Second harmonic generation (SHG) conversion efficiency were investigated to explore the NLO characteristics. The thermal behavior of the crystals has been investigated by TG/DTA analyses. Keywords: Crystal growth; Solution growth; Nonlinear optical material